ESTIMATION OF AGRICULTURE SAVE GARUT CHIPS WITH ACCELERATED TEST METHOD - Chayati, Ichda (Jurnal Penelitian Saintek, 2015)
ion of shelf life 0/ arrowroot chips by accelerated test was ’I1Ialea, Arrowroot chips from KKPA was fried, packed, and kept at and -IO"C and room temperature. followed by hedonic lest and ..,...snemtcut analysis. Chemical compositions of arrowroot chips were 4.97 % moisture, ]05 % ash.].:/7 % protein, ]715 % fat, 62.7 % (by difference) and -I.M % crude fiber content.’ Arrowroot chips fried with good quality frying oil and packed with plastic 05 has /5 weeks shelflife bv estimation If it is kept at room